The effect of Propolis and Xylitol chewing gums on salivary Streptococcus mutans count: A clinical trial - Sneha Girdhari Tulsani; Nagarathna Chikkanarasaiah; Shakuntala Bethur Siddaiah; Navin H Krishnamurthy (Wolters Kluwer Medknow Publications, 2014)
Background: Streptococcus mutans is one of the most common cariogenic microorganisms. Use of natural anticariogenic agents, such as Xylitol has been well-established in the literature. On the other hand, there is a scarcity of studies that have reported the antimicrobial potential of Propolis as an anticariogenic chewing agent; hence, the present study was designed. Aims: To evaluate and compare the anticariogenic action of two commercial chewing gums Propolis and Xylitol on the salivary S. mutans count in a group of children from Bengaluru city. Settings and Design: Clinical setting and experimental design. Materials and Methods: Thirty healthy children aged 8-11 years with decayed, missing, and filled teeth (dmft)/DMFT index score ≥3 were included in the study. Before the test, unstimulated saliva was collected. Children divided into Group I and II were given Propolis and Xylitol chewing gums respectively; to chew for 15 min. Saliva samples were then collected at 15 min (just after spitting) and after 1 h. The amount of S. mutans in saliva was evaluated using a selective media (MSAB). In addition, compliance of the two chewing gums among the children was tested with a questionnaire. Statistical Analysis Used: Student's t-test. Results: Six samples out of 30 were excluded due to no growth. The total number of bacterial colonies was significantly reduced when compared to baseline in both the groups. Propolis gum showed statistically significant reduction in the number of colonies as compared to Xylitol. Xylitol gum was more preferred than Propolis gum by the children. Conclusions: Propolis chewing gum can be used as an anticariogenic agent in children.